A solid-state fluorescence sensor for nitroaromatics and nitroanilines based on a conjugated Calix[4]arene polymer - Prata, José V. (2020)
A new conjugated polymer possessing calix[4]arene-oxacyclophane units wired-in-series by phenyleneethynylene linkers was synthesized by a Sonogashira-Hagihara cross-coupling method in high yield. The polymer was structurally characterized by FTIR and 1H/13C/HSQC NMR techniques, and its average Mn (38.5 kDa) retrieved from GPC analysis. The polymer is highly emissive (ΦF =0.55) and exhibits a longer-than-usual excited-state lifetime (1.80 ns) for a phenyleneethynylene type polymer. Similar photo physical properties (absorption and fluorescence emission) were observed in solution and insolid-state. This stems from the presence of bulky calixarene moieties along the polymer chains which prevent interchain staking and the formation of ground-state aggregates and/or non-emissive exciplexes, both deleterious to solid-state materials envisioned for fluorescence sensing applications. Moreover, the intrinsic molecular recognition capabilities of its two rigid inner cavities (calixarene and cyclophane sub-units), allied with the high three-dimensionality of the macromolecule that creates additional interstitial voids around the molecular receptors, can boost its sensory responses towards specific analytes. A high sensitive response was observed in the detection of nitroaromatics and nitroanilines in neat vapour phases by casted films of the polymer. The largest sensitivitieswereobtainedfor2,4-dinitrotoluene (a taggant for the explosive TNT;>85% of fluorescence quenching upon 1 min exposure) and ortho-nitroaniline (90% of emission reduction in 30s).The sensory responses attained in solid-state are discussed on the basis of the electron affinities of the analytes and their electrostatic interactions with polymer films.